2021
DOI: 10.1021/acscentsci.1c00919
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Fluorescent Akt Biosensor Reveals Lysosome-Selective Regulation of Lipid Second Messengers and Kinase Activity

Abstract: The serine/threonine protein kinase Akt regulates a wide range of cellular functions via phosphorylation of various substrates distributed throughout the cell, including at the plasma membrane and endomembrane compartments. Disruption of compartmentalized Akt signaling underlies the pathology of many diseases such as cancer and diabetes. However, the specific spatial organization of Akt activity and the underlying regulatory mechanisms, particularly the mechanism controlling its activity at the lysosome, are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…This allowed us to clearly detect nuclear AMPK activity, which has posed a challenge for FRET-based AMPKARs 16 , 17 . Future engineering efforts will focus on enhancing the dynamic range of some of the subcellularly targeted variants, as mito-ExRai AMPKAR exhibited a reduced dynamic range compared to an untargeted counterpart, presumably due to close proximity with membranes, as we have seen previously with other targeted biosensors 16 , 57 . We found that switching the reporting unit could affect the kinetics of the response (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…This allowed us to clearly detect nuclear AMPK activity, which has posed a challenge for FRET-based AMPKARs 16 , 17 . Future engineering efforts will focus on enhancing the dynamic range of some of the subcellularly targeted variants, as mito-ExRai AMPKAR exhibited a reduced dynamic range compared to an untargeted counterpart, presumably due to close proximity with membranes, as we have seen previously with other targeted biosensors 16 , 57 . We found that switching the reporting unit could affect the kinetics of the response (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Measured as the ratio of fluorescence intensities at these two excitation wavelengths, the PKA-stimulated response from ExRai-AKAR is up to 3-fold higher than optimized FRET-based AKARs, making ExRai-AKAR the most sensitive kinase sensor at the time. Much like the original AKAR spawned a large family of FRET-based KARs, the generalizable design of ExRai-AKAR has also yielded a series of highly sensitive reporters for other kinases, such as PKC and Akt ( Chen et al, 2021 , Mehta et al., 2018 ). At the same time, we realized that ExRai-AKAR can be further optimized through directed evolution by targeting its short linker regions, given the importance of linker sequences in biosensor engineering ( Akerboom et al., 2012 ; Dana et al., 2019 ; Miyawaki et al., 1997 ; Hires et al., 2008 ; Nakai et al., 2001 ; Patriarchi et al., 2018 ).…”
Section: Before You Beginmentioning
confidence: 99%
“…The following protocol describes the use of the FRET-based Akt activity reporter 2 (Ak-tAR2) and Akt-STOPS that are genetically targeted to specific subcellular locations to track and perturb, respectively, Akt activity in NIH3T3 cells, in response to PDGF stimulation (Chen, Sun, Zhong, Zhou, & Zhang, 2021;. Briefly, NIH3T3 cells are transfected with plasmid DNA encoding AktAR2 either alone, to assess cellular Akt activity induced by growth factors, or in combination with Akt-STOPS, to evaluate the inhibition of Akt activity by Akt-STOPS.…”
Section: Visualizing and Perturbing Subcellular Akt Kinase Activity U...mentioning
confidence: 99%
“…Furthermore, an allosteric lipid switch model for cellular Akt activation has been proposed, which suggested that phosphorylated, active Akt is restricted to 3‐PI‐containing membranes, and association with 3‐PI prevents the dephosphorylation and deactivation of Akt (Ebner, Lucic, Leonard, & Yudushkin, 2017; Yudushkin, 2020). Using subcellularly targeted AktARs, we detected Akt activity at various membrane compartments (Chen et al., 2021; Gao & Zhang, 2008; Zhou et al., 2020). In particular, 3‐PIs, which predominantly accumulate at the plasma membrane, unexpectedly accumulate at the lysosomal membrane in response to growth factor stimulation, specifically promoting lysosomal Akt/mTOR signaling (Chen et al., 2021).…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation